Effect of poly(amic acid) and polyimide on the adhesive strength and fracture toughness of epoxy resin - Bakar, М.; Okulska-Bożek, М.; Zygmunt, М. (Фізико-хімічна механіка матеріалів, 2011)
The present work investigates the effect of polyimide and poly(amic acid) content on the properties of epoxy resin. Charpy impact strength increased by 80% and 70% with the addition of 10 wt.% poly(amic acid) and 15 wt.% polyimide, respectively. However, the flexural strength was improved by 95% and 73% (in comparison with neat epoxy resin) by the addition of 5 wt.% polyimide and 5 wt.% poly(amic acid), respectively. Moreover, the addition of 10 wt.% polyimide resulted in two fold increase of impact adhesive strength, while the tensile adhesive strength of epoxy was increased by 70% with only 5 wt.% polyimide. Infrared spectra showed that the obtained compositions containing polyimide or poly(amic acid) exhibited a semi-interpenetrating polymer networks structures, characterized by a relatively high flexibility and very good mechanical properties. Досліджено вплив вмісту полііміду (PI) та поліамідної кислоти (PAA) на властивості епоксидної смоли. Виявлено, що після додавання 10% PAA та 70% PI ударна в’язкість збільшується, відповідно, на 80 та 70% порівняно з немодифікованою смолою. З додаванням у полімер 5% PI та PAA міцність на згин підвищується, відповідно, на 95 та 73%. Крім того, за вмісту 10% PI вдвічі збільшилась адгезійна міцність за удару, а за вмісту 5% PI адгезія за розриву зросла тільки на 70% порівняно з немодифікованою смолою. Інфрачервона спектроскопія показала, що композиції епоксидної смоли з PI та PAA мали напіввзаємопроникні сітчасті структури з відносно високими еластичністю та механічними характеристиками. Исследовано влияние содержания полиимида (PI) и полиамидной кислоты (PAA) на свойства эпоксидной смолы. Выявлено, что после добавления 10% PAA и 70% PI ударная вязкость увеличивается, соответственно, на 80 и 70% в сравнении немодифицированной смолой. С добавлением в полимер 5% PI и PAA прочность на изгиб увеличивается, соответственно, на 95 и 73%. Кроме того, при содержании 10% PI вдвое увеличилась адгезионная прочность при ударе, а при содержании 5% PI адгезия при разрыве возросла только на 70% в сравнении с немодифицированной смолой. Инфракрасная спектроскопия показала, что композиции эпоксидной смолы с PI та PAA имели полувзаимопроникаемые сетчатые структури с относительно высокими эластичностью и механическими характеристиками.